Biological and actual grain yield of wintering oats in the conditions of the South foothill zone of the North-West Caucasus - М. V. Kuzenko (Новые технологии, 2022)
The assessment of biological and actual grain yields, as well as the results of studying the percentage of realization of biological yields of varieties of wintering oats of various uses cultivated in soil and climatic conditions of the south foothill zone of the Northwest Caucasus, showed the advantage of grain-type varieties. For comparison, the grain yields of 2018 and 2020 were taken. with differences in the amount of precipitation during the most important period of culture development – the grain filling phase. In the conditions of the first year of research, the grain yield of wintering oats was 100–147 g/m2 and it ranged from 288 g/m2 (Guzeripl) to 438 g/m2 (Oshten) in 2019–2020. Biological yield in 2018 was formed at the level of 150–245 g/m2. In more favorable weather conditions in 2020, the level of biological yield varied from 436 g/m2 (Oshten) to 902 g/m2 (Verny). For two years of research, the average value of biological yield was 293–540 g/m2. The number of plants was: 2018 – 100–124 pcs./m2, 2020 – 132–224 pcs./m2. Grain weight varied from 1,3 to 1,8  g (2018), in 2020 it was 2,3–4,9 g. On average, over two years, the number of plants varied from 124 pcs./m2 (Guzeripl) to 174 pcs./m2 (AGU 75), the grain weight was 1,9–3,2 g. Studies have found that the most highly productive varieties are Oshten, AGU 75, Mezmai. The Verny variety is distinguished by a high biological yield of grain, Oshten is characterized by the highest percentage of biological yield realization.